Existing Curriculum Management in Enhancing Nazhir's Professionalism; Analysis Network Process - Rusli, Radif Khotamir; Hafidhuddin, Didin; Bahruddin, Ending; Tamam, Abas Mansur (JURNAL AL-TANZIM, 2023)
Nazir's profession is an educational program with little attention to Islamic Education. Therefore, an alternative solution is needed to increase Nazir's professionalism through curriculum management. This study aims to identify existing curriculum management and then analyze and develop the model to find a new curriculum. The qualitative research method is based on the Analytic Network Process (ANP) decision-making strategy to obtain a curriculum model for the Nazir professional program. The study results show that the training curriculum at LSP focuses on two scopes: waqf program planning and implementation. The curriculum developed through ANP decision-making produces four competencies: religious knowledge competence, communication competence, social science competence, and moral competence. The curriculum structure can be applied to one level of Nazir professional education, with the condition that each Nazir candidate has a bachelor's degree from various disciplines, particularly Islamic Religious Education. The findings of this study revealed that the respondents agreed with a very high rate agreement of 88.2% that a professional Nazir could be formed using the curriculum of the four competency-based Nazir waqf professional programs.